Exploiting Stokes and anti‐Stokes type emission profiles of aptamer‐functionalized luminescent nanoprobes for multiplex sensing applications. Issue 21 (1st June 2018) - Yüce, Meral; Kurt, Hasan; Hussain, Babar; Ow‐Yang, Cleva W.; Budak, Hikmet
Abstract: Multiplex biosensing of four types of bacterial food pathogens in one pot is described. Stokes and anti‐Stokes type photoluminescence (PL) of two quantum dots (QD) and two upconverting nanoparticles (UCNP) were utilised for realisation of the multiplex detection. The biosensing system was composed of aptamer‐functionalized QD and UCNP nanoprobes that were conjugated with partially complementary DNA‐modified magnetic beads for separation. PL signals of the conjugates were collected before and after incubation with target pathogens in one pot through the sequential excitations at 335 nm for QD probes and 980 nm for UCNP probes. The limit of detection values achieved were 28, 15, 12 and 25 cfu⋅mL −1 for Listeria monocytogenes, Staphylococcus aureus, Salmonella typhimurium and Pseudomonas aeruginosa, respectively. Efforts for extending the multiplex detection up to five pathogens were also presented even though the PL signal cross‐talk of a third QD nanoprobe hindered the detection. This work empowers co‐deployment of QDs and UCNPs and paves the way for future studies in multiplex sensing, labelling, and bioimaging fields. Abstract : Multiplex detection of food pathogens in a single test tube was presented. Co‐employment of Stokes and anti‐Stokes type luminescent nanoparticles and high specificity of ssDNA aptamers enabled the detection of four pathogens in one pot. This work may pave the way for more sophisticated multiplex systems for use in biosensing and bioimaging applications.